Time‐integrated δ2H in n-alkanes and carbohydrates from boreal needles reveal intra-annual physiological and environmental signals - Angove, Charlotte; Wiesenberg, Guido L. B.; Lehmann, Marco M.; Saurer, Matthias; Tang, Yu; Sahlstedt, Elina; Speckert, Tatjana C.; Schiestl‐Aalto, Pauliina P.; Rinne‐Garmston, Katja T. (John Wiley & Sons, 2025)
Reliable insights from key δ2H bioindicators, n-alkanes and carbohydrates, are hindered by our limited understanding of isotope fractionation processes related to leaf water and primary assimilates. We addressed this with the first study to investigate time-integrated intra-annual δ2H signals of n-alkanes and carbohydrates in a natural forest. We sampled 1-yr-old needles (1N) and current-year needles (0N) from five Scots Pine trees in a coniferous forest in Hyytiälä, Finland, biweekly during 2019. The δ2H of their n-alkanes (δ2Halkane), water-soluble carbohydrates (δ2HWSC) and starch (δ2Hstarch) were evaluated for time-integrated physiological (gas-exchange) and environmental (hydrological) signals. Time integration was critical for interpreting δ2HWSC and δ2Halkane. Time-integrated net assimilation rate (T:An), the strongest signal in δ2HWSC, correlated negatively with 1N δ2HWSC (early season) and positively with 0N δ2HWSC (late season). Unexpectedly, δ2Halkane exhibited stronger environmental signals in 1N than in 0N, with the most pronounced being physiologically mediated hydrological signals. T:An is a major signal in intra-annual δ2HWSC in a boreal forest, subject to seasonal interactions with needle age and δ2Hstarch. There could be enough de novo n-alkane synthesis in situ to enhance the reliability of δ2Halkane as a hydrological indicator, bringing promise to interpretations of the n-alkane palaeohydrological record.
Keywords: bioindicators; deuterium; forests; isotopes; leaf sugar; leaf water evaporative enrichment; lipids; paleohydrology